KESALAHAN PENERAPAN HUKUM SEBAGAI ALASAN KASASI TINDAK PIDANA TURUT SERTA MEMALSUKAN SURAT SECARA BERLANJUT - Raflyansyah, Arief Agha; Septiningsih, Ismawati (Sebelas Maret University, 2023)
This legal research aims to find out the misapplication of the law by the District Court Judge as the reason for the Public Prosecutor's cassation against the acquittal in the criminal case of participating in forging letters related to the provisions of Article 253 paragraph (1) of the Criminal Procedure Code and the suitability of the Supreme Court's consideration in examining and deciding the Public Prosecutor's cassation in Supreme Court Decision Number 1086 K/Pid/2022. This legal research is a prescriptive and applied normative legal research with a case study approach. The source of legal material for this research comes from primary legal materials and secondary legal materials. The legal material collection technique used is document study or literature study. The technique of analyzing legal materials in this study uses the syllogism method with deductive thinking patterns. The results of the research and discussion obtained are that the Public Prosecutor can prove the suitability of the reasons for cassation submitted by him with the reasons for cassation contained in Article 253 paragraph (1) of the Criminal Procedure Code, namely in terms of whether it is true that a legal rule is not applied or applied improperly. Therefore, the Supreme Court granted the cassation of the Public Prosecutor and found the defendant guilty of committing the crime charged, then imposed a prison sentence of 6 (six) month.Keywords: Cassation, Mail Forgery, Acquittal Decision.